Partisipasi Masyarakat dalam Program Kampung Wani Jogo Suroboyo di Bratang Gede Kota Surabaya - Dhea Inayatul Maula; Deasy Arieffiani (Public Sphere Review, 2022)
Covid-19 is a virus that has spread throughout the world, including Indonesia. Mayor Regulation No. 67 of 2020 regarding the handling of Covid-19, hereby the Surabaya City government wants to improve civil society by empowering the RT/RW level community through the formation of a Covid-19 handling task force, by establishing the KampungWani Jogo Suroboyo. The purpose of this research is to determine Community Participation in the Bratang Gede area, Ngagel Rejo village, in the implementation of the Program Kampung Wani Jogo Suroboyo and the supporting and inhibiting factors for the implementation of the Program KampungWani Jogo Suroboyo. The benefit of this research is to broaden the reader's knowledge regarding community participation in dealing with the Covid-19 pandemic. The method used in this research is a qualitative method with a case study approach using the theory of Community Participation, according to Huraerah, 2008. The results of this research indicate that Community Participation in the Covid-19 Pandemic Period in the Program Kampung Wani Jogo Suroboyo has been running quite well in accordance with existing regulations, namely Mayor Regulation No. 67 of 2020. This program is also supported by sufficient human resources and adequate infrastructure. However, the obstacles in using the Lawancovid application do not work well and residents obtain funding independently using village cash.